Penentuan Kandungan Vitamin D2 Pada Ekstrak Etil Asetat Jamur Sawit (Volvariella volvacea) Dengan Metode Spektrofotometeri UV-Vis - Oky Hermansyah; Apriyanti Apriyanti; Suci Rahmawati; Rose Intan Perma Sari; Dwi Dominica (Poltekkes Kemenkes Bengkulu, 2026)
Numerous studies have demonstrated that vitamin D plays a significant role not only in bone health but also in immunity, aiding recovery from infectious respiratory diseases, diabetes, and cholesterol-related conditions. One natural source of vitamin D is mushrooms. Many studies have reported the vitamin D content in mushrooms such as oyster or paddy straw mushrooms, but none have reported the vitamin D content in palm oil mushrooms (Volvariella volvacea). These palm oil mushrooms are abundant in palm oil-producing regions such as Bengkulu Province, specifically in Pino District. This study aims to determine the vitamin D (ergocalciferol) content in the ethyl acetate extract of palm oil mushrooms harvested around oil palm plantations in Pino District. The palm oil mushrooms were processed into simplisia and extracted using ethyl acetate solvent through maceration, then evaporated to obtain a concentrated extract. The extraction process yielded a percentage of 1.076%. The vitamin D content in this concentrated extract was then determined using UV-Vis spectrophotometer with Vitamin D2 (ergocalciferol BPFI) as the standard. The test results produced a standard curve for Vitamin D solution with a regression coefficient (r) of 0.997 and a linear equation of y = 0.0337x + 0.011. The sample absorbance was plotted into the linear equation and its concentration calculated, resulting in a vitamin D2 (Ergocalciferol) content in sample. This study concludes that palm oil mushrooms obtained from around the oil palm plantations in Pino District, Bengkulu Province, contain vitamin D2 (ergocalciferol) at a level of 0.993% or approximately 397.200 IU/gram.